2011
DOI: 10.1007/s12088-011-0154-x
|View full text |Cite
|
Sign up to set email alerts
|

Street Vended Food in Developing World: Hazard Analyses

Abstract: Street food vending has become an important public health issue and a great concern to everybody. This is due to widespread food borne diseases, due to the mushrooming of wayside food vendors who lack an adequate understanding of the basic food safety issues. Major sources contributing to microbial contamination are the place of preparation, utensils for cooking and serving, raw materials, time and temperature abuse of cooked foods and the personal hygiene of vendors. Various studies have identified the source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
203
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(245 citation statements)
references
References 38 publications
3
203
1
9
Order By: Relevance
“…(57.1%, Table 1) in Kisangani was very high as compared to that of, for example, in Mexico (5%) (Estrada-Garcia et al, 2004). According to Rane (2011), the contamination of street food due to Salmonella sp. can be explained by the use of dirty dishwater (from dirty dishes) or lack of good hygiene practices of vendors when handling street food.…”
Section: Food Quality: Tapc At 30°cmentioning
confidence: 87%
See 2 more Smart Citations
“…(57.1%, Table 1) in Kisangani was very high as compared to that of, for example, in Mexico (5%) (Estrada-Garcia et al, 2004). According to Rane (2011), the contamination of street food due to Salmonella sp. can be explained by the use of dirty dishwater (from dirty dishes) or lack of good hygiene practices of vendors when handling street food.…”
Section: Food Quality: Tapc At 30°cmentioning
confidence: 87%
“…This situation puts the health of the population at risk. According to Rane (2011) andGhosh et al (2007), street foods are perceived to be a major public health risk due to lack of basic infrastructure and services, difficulty in controlling the large numbers of street food vending operations because of their diversity, mobility and temporary nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, in various researches made in some countries, insufficiencies were found out relating with application of hygiene and sanitation, preparation of food, food safety rules and knowledge of street food sellers. Poor hygiene, difficulty in obtaining drinking water, not removing wastes and similar environmental problems and the fact that street food are exempt from legal legislations, all these factors increase risks in ensuring food safety (Rheinlander et al, 2008;Omemu and Aderoju, 2008;Abdalla et al, 2009;WHO, 2010;FAO, 2011;Choudhury et al, 2011;Rane, 2011;Kealesitse and Kabama, 2012). Food origined pathogens are seen as a health threat during preparation and protection stages depending on the type of food.…”
Section: Evaluation Of Street Food As Regards To Hygiene Quality Anmentioning
confidence: 99%
“…It was observed that these foods were cooked well in advance of consumption. Time and temperature abuse are said to be the major factors that contribute to foodborne disease (Rane, 2011;Harrington, 2010;Shimoni et al, 2006;Bhowmik, 2005). In the Philippines, it was established that meatcontaining dishes were the common causes of the outbreaks, with spaghetti as the leading food vehicle (Azanza, 2006).…”
Section: Microbiological Analysismentioning
confidence: 99%